Tau-Theory-Based Visual Cueing Method For Obstacle Avoidance - Esmek, C.C.; Tauro-Padival, R.; Feigh, K.M.; Prasad, J.V.R. (My University, 2024)
Low situational awareness (SA) when operating close to terrain and obstacles significantly increases risk by dramatically reducing reaction times. This study aims to facilitate real-time trajectory adjustments and improve pilot SA without increasing cognitive load by focusing on the specific challenge of maneuvering around obstacles in hostile and degraded visual environments (DVE). This methodology is intended to improve the safety and efficiency of low-altitude rotorcraft missions. In addition to the bank angle cueing methodology, this study proposes a deceleration and rate of climb cueing methodology and decision logic to provide a smooth transition between each cue under appropriate circumstances. A 3D conformal symbology is designed using the Blender software, a basic simulation environment is created in Unreal Engine, and several desktop simulations are performed in the MATLAB/Simulink environment using pilot models. The primary objective of these studies is to lay the groundwork for future pilot-in-the-loop simulations by designing a framework that could potentially integrate this cueing method into a simulator environment where the cues are presented to the pilot as a 3D conformal symbology set using a Heads-Up Display (HUD). This preliminary work is intended to enhance the potential effectiveness of the pilot's cueing system in hostile and degraded visual environments once actual testing and implementation are underway.